Family reunion : [large type] a novel - Thayer, Nancy, 1943- (Center Point Large Print, 2021)
"Fresh off the heels of her college graduation, Eleanor's dear granddaughter, Ari, has just ended an engagement that felt less like true love and more like a chore. She longs for a change of scenery and to venture far from her parents' snobbish expectations. Taking advantage of her newfound freedom, she heads to Nantucket to clear her head before graduate school, moving in with her grandmother and taking a job at the local beach camp. As she watches Eleanor begin to form a bond with an old acquaintance, Ari herself becomes completely smitten with a friend's charming older brother. But just as grandmother and granddaughter fall into a carefree routine, a few shocking discoveries throw them off course, and their ideas of the future seem suddenly uncertain"--